Risk Assessment in Thyroid Lobectomy and Total Thyroidectomy using Over 100 Thousand Cases. (December 2021) - Brauer, Philip R.; Burkey, Brian B.; Reddy, Chandana A.; Lamarre, Eric D.
Objectives: To assess risk factors and non-thyroid specific postoperative complications for thyroid lobectomy compared to total thyroidectomy. Methods: A retrospective, cross-sectional study of adults undergoing a lobectomy or total thyroidectomy using the National Surgical Quality Improvement Program database between 2005 and 2017. Patients not treated by otolaryngologists or general surgeons and with unknown demographic variables were excluded. Results: A total of 106 915 patients were analyzed, 64 763 total thyroidectomies and 42 152 lobectomies. Multivariable analysis demonstrated that total thyroidectomy patients were half as likely to return to the operating room (OR = 0.491 (95%CI 0.445-0.542), P  < .001). Within this cohort, patients at greater risk for reoperation had a history of hypertension (OR = 1.225 (95%CI 1.090-1.376), P  < .001), a malignant pathology (OR = 1.921 (95%CI 1.734-2.128), P  < .001), and smoked (OR = 1.237 (95%CI 1.087-1.407), P  = .001). Conversely, diabetes and body mass index did not impact the rate of reoperation when assessing total thyroidectomy and lobectomy. The most frequent non-thyroid specific complications in total thyroidectomy were unplanned intubation (0.5%), urinary tract infection (0.3%), and superficial surgical site infection (0.3%). In thyroid lobectomy, the most common complications were superficial surgical site infection (0.3%) and urinary tract infection (0.2%). Conclusions: Our multi-institutional study indicates specific risk factors for returning to the operating room that may warrant closer follow up after surgery for total thyroidectomy or thyroid lobectomy. We also identified the most common post-operative complications. During pre-operative planning, these findings should be considered by thyroid surgeons to help mitigate risk to patients.